The Analysis of Students’ Common Errors in Constructing Passive Voice in Explanation Text by English Department Students in Universitas Negeri Padang - Rahma Hayuni; Witri Oktavia (Universitas Negeri Padang, 2022)
This study was aimed to describe students’ common errors in constructing passive voice in explanation text by English Department Students of Universitas Negeri Padang who took Academic Writing class. It was aimed to find students common errors in writing explanation text. This research was descriptive method research. The sample of this research was the K2-K5 2019 students. The research was taken based on simple random sampling. This research was conducted by using students’ final writing test in academic writing from 27 students in order to find the common error in students’ writing. The finding show that the most common error made by the students’ in constructing passive voice were omission error with 47 errors with 22 omission errors in auxiliary be, 20 omission errors in auxiliary to be and 5 omission errors in preposition. Misinformation errors 24 errors in total with 18 errors in misinformation auxiliary, 5 errors in misinformation past participle